Roadmap for Sustainable Mixed Ionic-Electronic Conducting Membranes - Chen, G.; Feldhoff, A.; Weidenkaff, A.; Li, C.; Liu, S.; Zhu, X.; Sunarso, J.; Huang, K.; Wu, X.Y.; Ghoniem, A.F.; Yang, W.; Xue, J.; et al. (WILEY-V C H VERLAG GMBH, 2022)
Mixed ionic-electronic conducting (MIEC) membranes have gained growing interest recently for various promising environmental and energy applications, such as H2 and O2 production, CO2 reduction, O2 and H2 separation, CO2 separation, membrane reactors for production of chemicals, cathode development for solid oxide fuel cells, solar-driven evaporation and energy-saving regeneration as well as electrolyzer cells for power-to-X technologies. The purpose of this roadmap, written by international specialists in their fields, is to present a snapshot of the state-of-the-art, and provide opinions on the future challenges and opportunities in this complex multidisciplinary research field. As the fundamentals of using MIEC membranes for various applications become increasingly challenging tasks, particularly in view of the growing interdisciplinary nature of this field, a better understanding of the underlying physical and chemical processes is also crucial to enable the career advancement of the next generation of researchers. As an integrated and combined article, it is hoped that this roadmap, covering all these aspects, will be informative to support further progress in academics as well as in the industry-oriented research toward commercialization of MIEC membranes for different applications.